English Speaking Skills Assessment in the "English on Tuesday" Program: a Cipp-Based Evaluation Approach - Luthfiyanti, Witri; Aliyah, Nisa; Arya, Dhika (Journal of English Education and Teacher Trainer, 2025)
This study evaluates the speaking assessment component of the "English on Tuesday" program at Al-Irhaam Elementary School, Bandung, a vocabulary enrichment initiative for primary school students in Grades 1-6. Using the Context, Input, Process, and Product (CIPP) evaluation framework, the research examines how speaking tasks embedded in the program affect young learners' oral proficiency. The context evaluation emphasizes the program's relevance to students' communicative needs and motivation to use English in daily school activities. The input evaluation demonstrates that multimedia materials, vocabulary lists, and simple phrase patterns serve as the foundation for speaking practice, supported by educational videos and interactive digital games. The process evaluation indicates that speaking activities, including sentence construction, role-playing, and oral reporting, promote dynamic and engaging language use among students aged 6-12 years old. The product evaluation reveals significant improvements in students' fluency, confidence, and ability to apply vocabulary in meaningful contexts, as documented through teacher reflection journals, classroom observations, and student speaking samples collected over one academic semester. The findings indicate that integrating structured speaking tasks with vocabulary learning, accompanied by age-appropriate resources and interactive approaches, can considerably improve speaking skills in early English language instruction. This study provides practical insights into developing effective formative speaking assessments for vocabulary-focused programs targeting young learners in Indonesian elementary school contexts.